1966
DOI: 10.1126/science.152.3728.1499
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectra from Three Cosmic Sources

Abstract: Three cosmic x-ray sources have been observed from a water-launched rocket carrying two x-ray detectors to an altitude of 200 kilometers. The x-ray spectra, measured in the photon energy range between I and 40 kiloelectron volts, are all different. The sources in order of hardness of spectra are Cyg XR-1, Tau XR-1, and Sco XR-1. The intensity of Sco XR-J decreased at low photon energies. The differences in spectra might source mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1968
1968
1973
1973

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…These spectra were a factor of two less than some early proportional counter measurements (Chodil et al 1965;Grader et al 1966;Hayakawa, Matsuoka, and Yamashita 1966) but were consistent with the less accurate flux measurements made by other early experimenters (Bowyer et al 1964;Giacconi, Gursky, and Waters 1965). Manley (1967) has suggested that the discrepancy was instrumental in origin and did not represent a real variation.…”
Section: Pectrasupporting
confidence: 85%
“…These spectra were a factor of two less than some early proportional counter measurements (Chodil et al 1965;Grader et al 1966;Hayakawa, Matsuoka, and Yamashita 1966) but were consistent with the less accurate flux measurements made by other early experimenters (Bowyer et al 1964;Giacconi, Gursky, and Waters 1965). Manley (1967) has suggested that the discrepancy was instrumental in origin and did not represent a real variation.…”
Section: Pectrasupporting
confidence: 85%
“…The data points presented were specifically analyzed for evidence of interstellar absorption at lower energies, but no statistically significant absorption was needed to produce a fit to a spectrum characteristic of either bremsstrahlung or synchrotron radiation. The power law spectrum characteristic of synchrotron radiation that Gorenstein et al derive is given by Equation (5); the continuous nature of the spectrum as observed by Grader et al (1966) andChodil et al (1967) between 10 and 20 keV (see Figures 4 and 29) favors the choice of the power law spectrum as a better representation of the observations. Meekins et al (1969) observed Cyg XR-1 with three thin window proportional counters aboard a rocket launched from White Sands, New Mexico at 0321 UT, September 8, 1967 (JD 2439741.64).…”
Section: B the Flux At Energies Between 1 And 20 Kevmentioning
confidence: 97%
“…Figure The flux observed from Cyg XR-1 was assigned by the authors to the energy interval between 1.5 and 15 keV; this is the position we have assigned it in Figure 31. Figure 4, discussed above, also contains observations of the flux of Cyg XR-1 at energies below 20 keV taken by Grader et al (1966). It was included in the earlier section of this paper because it also contained observations of the object at energies above 20 keV.…”
Section: B the Flux At Energies Between 1 And 20 Kevmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.1017/S0074180900100269 a quite significant fraction are associated with the region of the galactic nucleus . Unless these are objects of an entirely unexpected sort, many are pre sumably mass transfer binaries in the stellar population associated with the galactic nuclear region, viz., an old metal-rich population similar to the stars in galactic clusters like M 67 and N G C 7 5 2 (Arp, 1965;Van den Bergh, 1972) or globular clusters like M 71 (Arp and Hartwick, 1971) and N G C 6352 (Hartwick and Hesser, 1972). This means we are dealing with binary systems in which the primaries are of relatively low mass, i.e., in the range 1 to 2 m© (cf.…”
Section: Some Boundary Conditions On Possible Mass-transfer Modelsmentioning
confidence: 99%